Artificial Intelligence and Election in Nigeria: An Assessment of the Possible Impact on the Country’s Electioneering Process - Tajudeen, Abdullahi (Kashere Journal of Politics and International Relations, 2025)
The advancement in the field of Artificial Intelligence (AI) has significantly affected the electioneering process. This is true in terms of, for example, voters’ education and electoral debates. But also true is the fact that the adoption of artificial intelligence has the potential to derail the country's democratic achievement in terms of relatively free and fair elections. It is against this background that the study examines the possible impact of AI on elections in Nigeria. The framework of analysis adopted for this study is the innovation diffusion theory. Based on the analysis thereof, the study concluded that the adoption of AI into the electoral process has the potential to either play a positive or negative role depending on its utilization by the Independent Electoral Commission (INEC) and the regulations set by authorities to guide its adoption. The study recommended, among others, that the electoral management bodies, both at the national and state levels, should embark on public awareness campaigns to educate the electorates on the workings and capabilities of artificial intelligence as regards elections and electioneering process so as to curtail the possible impacts of artificial intelligence-generated misinformation and disinformation.